Tinjauan Hak Atas Kesejahteraan Sosial Terhadap Fakir Miskin di Kabupaten Jember - holifah, ilyatul; R. Hariandja, Tioma; Musfianawati; Alkahfi Setiawan, Sidi (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2024)
The poor are those who earn more than the poor but not enough tofulfill their basic needs. As the weakest and most vulnerable groupin society, the poor need public and social infrastructure in order toslowly break out of the poverty cycle around them. Poverty as asocial problem does not only involve economic problems, but alsoincludes other problems faced by the community. How is the form ofsocial welfare implementation based on regional regulations andhow is the form of social welfare implementation in the jemberdistrict, and its purpose is to find out and analyze how the form ofresponsibility of the Jember Regency Government towards the socialwelfare of the poor according to Jember Regency RegionalRegulation Number 8 of 2015 and to find out how the form of itsimplementation in the jember district through research at the socialservice. The research method used is using empirical methods,where the method of collecting data through research used to seelegal aspects in social interactions in society. The conclusion is thatthe government of Jember Regency must fulfill basic services for thepoor in Jember Regency and the government of Jember Regencymust fulfill the rights of the poor in accordance with RegionalRegulation Number 8 of 2015 concerning organizing social welfareto the poor. The government of Kabupaten Jember itself has severalwork programs to deal with the poor in Kabupaten Jember.